2011
DOI: 10.1152/ajpendo.00363.2011
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction and insulin resistance from the outside in: extracellular matrix, the cytoskeleton, and mitochondria

Abstract: Insulin resistance in skeletal muscle is a prominent feature of obesity and type 2 diabetes. The association between mitochondrial changes and insulin resistance is well known. More recently, there is growing evidence of a relationship between inflammation, extracellular remodeling, and insulin resistance. The intent of this review is to propose a potentially novel mechanism for the development of insulin resistance, focusing on the underappreciated connections among inflammation, extracellular remodeling, cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
72
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 62 publications
3
72
0
2
Order By: Relevance
“…In other models of lipid overload (e.g., models of insulin resistance in skeletal muscle), it has been postulated that mitochondrial abnormalities lead to the accumulation of ectopic lipids (9), in contrast to the hypothesis presented by Picard and coworkers, in which lipid accumulation seems to precede mitochondrial dysfunction in the animal model. Further limitations of the study include the lack of information with respect to body composition, the presence of metabolic syndrome, and the mode of mechanical ventilation.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…In other models of lipid overload (e.g., models of insulin resistance in skeletal muscle), it has been postulated that mitochondrial abnormalities lead to the accumulation of ectopic lipids (9), in contrast to the hypothesis presented by Picard and coworkers, in which lipid accumulation seems to precede mitochondrial dysfunction in the animal model. Further limitations of the study include the lack of information with respect to body composition, the presence of metabolic syndrome, and the mode of mechanical ventilation.…”
mentioning
confidence: 86%
“…Over several years just prior to the 2008 Olympics, epidemiological studies reported that patterns of associations between fine particulate air pollution and cause-specific mortality were consistent with the hypothesis that air pollution exposure contributes to pulmonary and systemic oxidative stress, inflammation, and associated increased risk of atherosclerosis and ischemic cardiovascular and obstructive pulmonary diseases (2, 7). Recent reviews of the expanding literature (8) and emerging evidence from the Multi-Ethnic Study of Atherosclerosis (9) suggest that there are likely multiple, complex, interdependent mechanistic pathways linking air pollution to cardiopulmonary disease, but also provide growing evidence that pulmonary and systemic oxidative stress and inflammation play important roles.…”
mentioning
confidence: 99%
“…A variety of extracellular and intracellular biological components has been implicated in impairment of insulin signaling. These include free fatty acids (15), branched-chain amino acids (16), steroid and stress hormones (17), cytokines (18), diacylglycerol, ceramides (15), and intracellular free radicals derived from mitochondria (19). Although many studies have supported the contribution of oxidatively modified biological molecules, nonoxidized metabolites have also been implicated in insulin resistance (15,20).…”
Section: Mechanisms Of Peripheral Insulin Resistancementioning
confidence: 99%
“…1 Individuals with obesity show chronic low-grade inflammation. 2,3 The expansion of white adipose tissue in obesity has been associated with increased proinflammatory cytokines, such as tumor necrosis factor-a (TNFa) and interleukin 6 (IL-6). 2 These inflammatory cytokines circulate in the blood and can have negative effects on peripheral inulin responsive tissues, such as skeletal muscle and liver.…”
Section: Introductionmentioning
confidence: 99%